TOOLS FOR DEVELOPING STUDENTS’ ENVIRONMENTAL COMPETENCE THROUGH AN INTEGRATIVE APPROACH - Sh.A. Abdurakhmanova (International Journal of Literature and Language Studies, 2026)
The development of environmental competence among students has become one of the priority objectives of higher education in the context of increasing global environmental challenges. This paper examines the pedagogical potential of an integrative approach in fostering students’ environmental competence. The study analyzes the concept of environmental competence, the necessity of its development, and the effectiveness of educational tools implemented through interdisciplinary integration. It is argued that an educational process organized on the basis of interdisciplinary cooperation contributes to the formation of environmental knowledge, practical skills, responsible attitudes, and value orientations necessary for sustainable development.